Superfab saves the day - Delaporte, Bérengère, 1979-; Leroy, Jean, 1975- (Owlkids Books, 2014)
With a large superhero costume collection, Superfab is the best-dressed superhero around, but his frequent costume changes often stop him for arriving in time to help people in trouble, until one day, his style sense may just save the day.